Upaya Peningkatan Hasil Belajar Lompat Jauh Gaya Jongkok Melalui Penggunaan Alat Bantu Pada Siswa Kelas VA SDN 1 Selang - Achmad Hufron (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
The purpose of this study was to improve the learning outcomes of the squat-style long jump through the use of assistive devices for grade VA students of SD Negeri 1 Interval in the 2019/2020 academic year. This research is a Classroom Action Research (CAR). The research was carried out in two cycles, each cycle consisting of planning, implementing actions, observing, and reflecting. The research subjects were students of class VA SD Negeri 1 Selang, Kebumen District, totaling 19 students. Sources of data come from teachers and students. The technique of data collection is the practical test of performance and observation. The validity of the data using the method triangulation technique. Data analysis used comparative descriptive statistical analysis techniques and critical analysis. The research procedure is a spiral model that is interconnected. The results showed that through the use of assistive devices, students' learning outcomes in the squat style long jump were improved from pre-action to cycle I and from cycle I to cycle II. The learning process in the pre-action has not used tools so that student learning outcomes are low. The increase occurred in the first cycle. Student learning outcomes increased even though it was not optimal. The implementation of the second cycle caused the students' squatting style long jump learning outcomes to increase so that they could support a quality learning. Lesson 2019/2020.